On pure phases of the Vannimenus model - Ganikhodjaev, Nasir; Uguz, Selman; Akin, Hasan; Temir, Seyit (2010)
One of the main problems of the Statistical Physics is to describe all Gibbs measures corresponding to the given Hamiltonian. It is well known that such measures form a nonempty convex compact subset in the set of all probabilistic measures. The purpose of this paper is to investigate Gibbs measures of the Vannimenus model.